Description of a new species of Sitana Cuvier, 1829 from southern India - Deepak, V.; Khandekar, Akshay; Varma, Sandeep; Chaitanya, R. (Zootaxa, 2016)
A new species of Sitana to the ponticeriana group is described herein from southern Tamil Nadu, India. Sitana marudhamneydhal sp.nov. is most similar to Sitana visiri, from which it differs in body scalation and dewlap size. Much like Sitana visiri, the breeding of this species coincides with the North-East monsoon rains (October to December), an adaptation related to its geographic location which receives higher rainfall during the North-East monsoon than the South-West monsoon.